2′,5′-oligoadenylates change the secondary structure and the functional activity of human S100A1 protein - Skorobogatov, O.Yu.; Zhukov, I.Yu.; Tkachuk, Z.Yu. (Reports of the National Academy of Sciences of Ukraine, 2015)
The results, which demonstrate the ability of 2′,5′-linked oligoadenylates to bind human S100A1 protein in vitro, thus causing alterations of its secondary structure, are presented. Such dimensional reorganization, in turn, affects protein's functional activity profile. With the use of spectroscopy methods, fluorescence, and circular dichroism, we have managed to detect small, but reliable changes in protein's secondary structure content upon the interaction with oligoadenylates, as well as alterations of its functional activity – the value of Ca2+ binding constant was shown to be increased. In our opinion, in vivo, 2′,5′-linked oligoadenylates interact with many other proteins, not only Ca2+ binding, thus affecting their activity.